Perineal burn contractures: An experience in tertiary hospital of a Himalayan state - Thakur S. Jagdeep; K. Diwana Vijay; Chand Chauhan Dayal; Thakur Anamika (Indian Journal of Plastic Surgery, 2008)
Perineal burn contracture is a rare burn sequel. We conducted a retrospective analysis of cases with perineal burn contractures managed in a tertiary care centre of a Himalayan state. We found that all cases sustained burn injury from burning firewood and the time of presentation was two to six years after the burn injury. We analyzed our treatment method and have classified these contractures into two types.